PIFs get BRright: PHYTOCHROME INTERACTING FACTORs as integrators of light and hormonal signals. Issue 4 (26th February 2014) - de Lucas, Miguel; Prat, Salomé
Summary: Light and temperature, in coordination with the endogenous clock and the hormones gibberellin (GA) and brassinosteroids (BRs), modulate plant growth and development by affecting the expression of multiple cell wall‐ and auxin‐related genes. PHYTOCHROME INTERACTING FACTORS (PIFs) play a central role in the activation of these genes, the activity of these factors being regulated by the circadian clock and phytochrome‐mediated protein destabilization. GA signaling is also integrated at the level of PIFs; the DELLA repressors are found to bind these factors and impair their DNA‐binding ability. The recent finding that PIFs are co‐activated by BES1 and BZR1 highlights a further role of these regulators in BR signal integration, and reveals that PIFs act in a concerted manner with the BR‐related BES1/BZR1 factors to activate auxin synthesis and transport at the gene expression level, and synergistically activate several genes with a role in cell expansion. Auxins feed back into this growth regulatory module by inducing GA biosynthesis and BES1/BZR1 gene expression, in addition to directly regulating several of these growth pathway gene targets. An exciting challenge in the future will be to understand how this growth program is dynamically regulated in time and space to orchestrate differential organ expansion and to provide plants with adaptation flexibility.   Contents     Summary 1126 I. Introduction 1126 II. Light and phytochrome signaling 1127 III. Phytochrome regulation of PIF activity 1128 IV. Developmental processes regulated by PIFs 1128 V. PIFs and hormonal control of light signaling 1129 VI. Role of PIFs in diurnal control of cell elongation 1132 VII. Response to vegetational shade 1135 VIII. PIF control of responses to elevated temperatures 1136 IX. Concluding remarks and future perspectives 1136   Acknowledgements 1137   References 1137